An orthogonal shim coil for 3T brain imaging. Issue 4 (21st October 2019) - Zhou, Jiazheng; Stockmann, Jason P.; Arango, Nicolas; Witzel, Thomas; Scheffler, Klaus; Wald, Lawrence L.; Lin, Fa‐Hsuan
Abstract : Purpose: We designed and implemented an orthogonal shim array consisting of shim coils with their planes perpendicular to the planes of neighboring RF coils. This shim coil improves the magnetic field homogeneity by minimizing the interference to RF coils. Methods: Using realistic off‐resonance maps of the human brain, we first evaluated the performance of shim coils in different orientations. Based on simulations, we developed a 7‐channel orthogonal shim array, whose coil plan was perpendicular to neighboring RF coils, at the forehead. A programmable open‐source current driver supplied shim currents. Results: The 7‐channel orthogonal shim array caused only marginal SNR loss to the integrated 32‐channel RF‐shim array. The 7‐channel orthogonal shim array itself improved the magnetic field homogeneity by 30% in slice‐optimized shimming, comparable to the baseline shimming offered by the scanner's 2nd order spherical harmonic shimming. Conclusion: Orthogonal shim coils can improve the field homogeneity while maintaining high image SNR.